Clinical impact of peroral endoscopic myotomy for esophageal motility disorders on esophageal muscle layer thickness - Watanabe, Daisuke; Tanaka, Shinwa; Kawara, Fumiaki; Abe, Hirohumi; Ariyoshi, Ryusuke; Nakano, Yoshiko; Takao, Toshitatsu; Morita, Yoshinori; Toyonaga, Takashi; Umegaki, Eiji; Kodama, Yuzo (Endoscopy International Open, 2019)
Background and study aims Previously, we reported that esophageal muscle layer thickness was associated with technical complexity of peroral endoscopic myotomy (POEM). However, there are no data regarding the mid-term effects of POEM procedures on esophageal muscle layer thickness. Therefore, we conducted this study to elucidate mid-term effects of POEM procedures, and to examine whether postoperative changes in esophageal muscle layer thickness were related to particular clinico-pathological features in patients with esophageal motility disorders. Patients and methods Seventy-four consecutive patients with esophageal motility disorders who underwent POEM at Kobe University Hospital from April 2015 to December 2016 were prospectively recruited into this study. First, we investigated the esophageal muscle layer thickness values obtained at 1 year after POEM. Second, we evaluated the effects of a reduction in muscle layer thickness on various clinico-pathological features. Results At 1 year after POEM, mean thickness of the inner circular muscle at 0 cm, 5 cm, and 10 cm from the esophagogastric junction was 1.06 ± 0.45 mm, 0.99 ± 0.36 mm, and 0.97 ± 0.44 mm, respectively. Among all sites, muscle layer thickness had significantly decreased after POEM. However, univariate logistic regression analysis demonstrated that no clinical factors were associated with esophageal muscle layer thickness after POEM procedure. Conclusions We demonstrated for the first time that thickness of the esophageal muscle layer was significantly decreased after POEM. This result reveals that changes in esophageal muscle layer thickness caused by esophageal motility disorders are reversible.